An Update in Epigenetics in Metabolic-Associated Fatty Liver Disease - Rodríguez-Sanabria, J. Samael; Escutia-Gutiérrez, Rebeca; Rosas-Campos, Rebeca; Armendáriz-Borunda, Juan S.; Sandoval-Rodríguez, Ana (Frontiers in Medicine, 2022)
Metabolic Associated Fatty Liver Disease (MAFLD) is characterized by hepatic steatosis accompanied by one of three features: overweight or obesity, T2DM, or lean or normal weight with evidence of metabolic dysregulation. It is distinguished by excessive fat accumulation in hepatocytes, and a decrease in the liver's ability to oxidize fats, the accumulation of ectopic fat and activation of pro-inflammatory pathways. Chronic damage will keep this pathophysiologic cycle active causing progression from hepatic steatosis to cirrhosis and eventually, hepatocarcinoma. Epigenetics affecting gene expression without altering DNA sequence, allows us to study MAFLD pathophysiology from a different perspective, in which DNA methylation processes, histone modifications, and miRNAs expression have been closely associated with MAFLD progression. However, these considerations also faced us with the circumstance that modifying those epigenetics patterns might lead to MAFLD regression. Currently, epigenetics is an area of great interest because it could provide new insights in therapeutic targets and non-invasive biomarkers. This review comprises an update on the role of epigenetic patterns, as well as innovative therapeutic targets and biomarkers in MAFLD.